Strategi Pengelolaan Dana Bantuan Operasional Sekolah Dasar Inpres Kecil Salena Kota Palu - Mohammad Reza Alfarid Yantu; Juliana Kadang; Darman Darman; Fatlina Z (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the management strategy for Operational Assistance Funds (BOS) at the Salena Small Inpres Elementary School, Palu City. This research uses a qualitative descriptive method with data collection techniques using in-depth interviews, observation and documentation. This research involved the school principal and BOS treasurer as primary data sources. Secondary data sources include the school profile, vision and mission, BOS Annual Activity Plan (RKT Annual Work Plan), BOS Accountability Report (LPJ Accountability Report), and teacher data. The results of the interviews were then transcribed into Indonesian. The results show that the BOS fund management strategy goes through several stages and processes, namely planning, management, evaluation and reporting. The planning, management, evaluation and reporting components show that the Salena Small Inpres Elementary School in Palu City has run well in accordance with the provisions of the technical guidelines for managing BOS funds. The obstacles that were found resulted in the implementation of these regulations being hampered by the school so that the program that had been prepared in the RKAS could not run well. Recommendations that can be given are periodic evaluations from stakeholders so that BOS funds can be managed effectively and efficiently.